MECHANISMS OF MANAGEMENT OF INTELLECTUAL POTENTIAL OF UKRAINE IN THE CONDITIONS OF FORCED POPULATION MIGRATION - Сімків, Ліля Євгенівна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The article examines the theoretical and methodological foundations and practical aspects of forming mechanisms for managing Ukraine's intellectual potential in the context of forced population migration. The author clarifies the concept of "intellectual potential of the state" as a strategic resource for the country's development, which includes the totality of the nation's intellectual assets embodied in the knowledge, skills, and competencies of citizens and the intangible assets of organizations. The main components of intellectual potential (human, structural, social, market, innovation, and cultural-value) are identified, which undergo transformations as a result of forced migration. Based on the analysis of statistical data, the current state of migration processes in Ukraine is examined and their key characteristics are determined: forced nature, significant proportion of highly qualified specialists among migrants, uneven regional distribution, and gender asymmetry of migration flows. The main challenges for the management system (risk of irreversible loss of human capital, regional imbalances, information deficit) and opportunities (formation of transnational professional networks, development of digital forms of activity, potential for "brain circulation") are identified. The author has developed a comprehensive system of mechanisms for managing intellectual capital, which includes institutional (creation of a National Agency, regional centers, interaction with the diaspora), organizational (migration monitoring, virtual mobility, infrastructure), legal (improvement of legislation, legal regimes for reintegration), and economic (specialized funds, grants, incentives, public-private partnerships) mechanisms. The necessity of their integration into a unified system that will function on the principles of systematicity, adaptability, proactivity, inclusiveness, and transparency is substantiated.